If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -9x = 171 + -44x Solving 6 + -9x = 171 + -44x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44x' to each side of the equation. 6 + -9x + 44x = 171 + -44x + 44x Combine like terms: -9x + 44x = 35x 6 + 35x = 171 + -44x + 44x Combine like terms: -44x + 44x = 0 6 + 35x = 171 + 0 6 + 35x = 171 Add '-6' to each side of the equation. 6 + -6 + 35x = 171 + -6 Combine like terms: 6 + -6 = 0 0 + 35x = 171 + -6 35x = 171 + -6 Combine like terms: 171 + -6 = 165 35x = 165 Divide each side by '35'. x = 4.714285714 Simplifying x = 4.714285714
| 6x-9=51 | | 12x^2-9=0 | | 49-5x=22x+19 | | 5x+10=-32-9x | | p(x)=-2x^2+120x-788 | | 6-8x=86-36x | | 63x^4+37x^2+4=0 | | -8k=7.7-7.2k | | 5x+31=14x-50 | | 0=x^3+2x^2+8x | | 2e-8= | | 3-ax+4x-36=0 | | x=5-y | | p=3 | | 7=0.5b+2.5 | | 15y+5y-6=17y | | 6y=y-23 | | 4x^2-12x+9=9 | | 12m-9=14m | | 12m-9=14 | | 2x+7=7x+2 | | 7(1-p)=-3(5+3q) | | 4a+4=35 | | 4f+8=8 | | 6(6a+10)=60+36a | | 4x^2-3x^2-6=0 | | 2x^2-3x-y=0 | | 2-(17-5x)=8(-4h+3) | | 2p=16+7p | | 3-2[6-(5y-6)]= | | 5x-27=28 | | 5t+7=2t |